Outcomes and predictors of cardiac events in medically treated patients with atrial functional mitral regurgitation. (1st October 2020) - Kim, Kitae; Kitai, Takeshi; Kaji, Shuichiro; Pak, Misun; Toyota, Toshiaki; Sasaki, Yasuhiro; Ehara, Natsuhiko; Kobori, Atsushi; Kinoshita, Makoto; Furukawa, Yutaka
Abstract: Background: Little is known about the outcomes and predictors of adverse cardiac events in medically treated patients with atrial functional mitral regurgitation (FMR). Methods: We screened 1405 consecutive patients with grade ≥ 3+ mitral regurgitation (MR) detected by echocardiography. After excluding patients with previous or early (within 3 months from diagnosis) mitral valve surgery, congenital heart disease, hypertrophic cardiomyopathy, severe aortic valve disease, or unknown etiology, the study population consisted of 319 patients with primary MR, 395 patients with FMR with left ventricular (LV) dysfunction, and 184 patients with atrial FMR. Atrial FMR was defined as FMR in patients without LV wall motion abnormality or dilatation. Results: The cumulative incidence of the composite of cardiac death and heart failure hospitalization at 3 years was 10.5% in primary MR, 37.5% in FMR with LV dysfunction, and 14.0% in atrial FMR ( p  < .001). In atrial FMR patients, LV end-diastolic volume index (hazard ratio [HR] 1.06, 95% confidence interval [CI] 1.02–1.10), severe MR (grade 4+) (HR 2.73, 95% CI 1.21–6.12), being symptomatic (NYHA ≥ 2) (HR 2.82, 95% CI 1.15–6.92), and having ≥1 comorbidities (HR 3.96, 95% CI 1.74–9.00) were independently associated with an increased risk for adverse cardiac events by a multivariable Cox regression analysis. Conclusions: Outcomes of medically treated patients with atrial FMR were better than those of FMR with LV dysfunction, but worse than those of primary MR. In atrial FMR patients, LV dilatation, severe MR, being symptomatic, and the presence of comorbidities were independently associated with an increased risk for adverse cardiac events. Highlights: Atrial functional mitral regurgitation occurs without left ventricular dysfunction. Little is known about the outcomes of atrial functional mitral regurgitation. Cardiac events were not uncommon (14% at 3 years) in medically treated patients. Left ventricular dilatation, severe regurgitation were independent predictors. Being symptomatic, the presence of comorbidities were also independent predictors.